Avaliação da qualidade do leite bovino produzido em propriedades leiteiras no semi-árido do Rio Grande do Norte, pelas boas práticas de produção - Souza, Carlos Henrique de (Universidade Federal Rural do Semi-Árido, 2010)
It was aimed to evaluate the quality of bovine milk after the application of Good Production Practices (GPP) on 10 dairy farms, located in semi-arid region of Rio Grande do Norte, from August to November 2009. Physico-chemical through ultrasonic analysis and microbiological analysis were obtained, verifying the presence of total and thermotolerant coliforms and mesophilic bacteria. The work was conducted in two stages. On the first stage, samples of milk were collected without educating producers about the GPP, on the second, the producers received guidance on the GPP, on how to eliminate the first three streams of milk, how to use the screened mug test, on cleaning the teats with chlorinated water, drying the teats with paper towels before milking and about using a strainer on the top of the milk tin at the property. Regarding the physical-chemical analysis, it was found that 93.4% of the fat, nonfat dry matter and protein averages were within the standards established by the current legislation. As for the microbiological aspects there was no significant difference between the numbers of total and thermotolerant coliforms before and after the GPP. However, the mesophilic bacteria count found a significant reduction (P> 0.01) after the use of GPP. Thus, confirming the importance of using GPP to improve the quality of bovine milk in the Brazilian semi-arid areas
Keywords: Produção de leite; Propriedades físico-químicas; Análises microbiológicas; Instrução Normativa 51; Milk production; Physic-chemical properties; Microbiological analysis; Normative Instruction 51; CIENCIAS AGRARIAS::MEDICINA VETERINARIA